Financial Ratios and Stock Price Predictability: A Study on Mobile Telecommunication Companies in Kuwait - AlAli, Musaed; AlAskar, Ibraheem T.; Aboualhasan, Husain S. (Finance & Economics Review, 2024)
Purpose: This paper aims to investigate the applicability of financial ratios derived from financial statements to predict the stock prices of mobile telecommunication companies in Kuwait. Methods: The pooled OLS regression method is used to examine the relationship between share prices (SP), as a dependent variable, against earnings per share (EPS), liquidity ratio (Liq), price to earnings (P/E) ratio, debt to equity (D/E) ratio, dividend yield (DY), and market to book value (M/B) ratio as independent variables. Results: Pooled OLS regression revealed that EPS and Liq have a statistically significant positive relationship with share prices, while the debt-to-equity (D/E) ratio shows a significant inverse relationship with share prices. Other factors under study did not show any significant relationship with share prices. Implications: The research results would help both investors and companies' top management identify the ratios that affect share price most. The results would help investors detect the factors that they should consider when making their investment decisions to improve their investment profitability and for the company's management to focus their efforts on improving these ratios to enhance shareholders' wealth. Originality: This study is a pioneering attempt to address the effect of financial ratios on the share prices of mobile telecommunication companies in Kuwait. Limitations: The relationship between financial ratios and share prices has been extensively researched and the results were very inconsistent which indicates that the effect of financial ratios on share price may vary from market to market.